ANALISIS PENERAPAN METODE ACTIVITY BASED COSTING DALAM MENENTUKAN HARGA POKOK KAMAR HOTEL PADA SIANTAR HOTEL - Silalahi, Evelin Roma Riauli; Purba, Rosmeldawati; Naibaho, Pani Romauli Elisabet (Jurnal Riset Akuntansi & Keuangan, 2024)
The purpose of this research is to determine the calculation of the cost of hotel rooms using the Activity Based Costing method and to compare the cost of hotel rooms between the traditional method and the Activity Based Costing method. The population in this study consists of data on direct costs, indirect costs, and other expenses incurred by Siantar Hotel from its establishment in 1913 to the present. The sample in this study is data on direct costs, indirect costs, and other expenses incurred by Siantar Hotel during the year 2023. Data collection was conducted using documentary techniques. The data analysis technique used in this study is descriptive quantitative analysis. The research results show that there is a difference in the cost of rooms, with the Activity Based Costing method resulting in lower costs compared to the traditional method. For President Suite rooms, the difference is Rp. 224,043; for Suite rooms, Rp. 74.188; for Deluxe rooms, Rp. 15.173; for Executive rooms, Rp. 22.652; for Superior rooms, Rp. 19.217; for Standar New rooms, Rp. 77,564; for Standar Single rooms, Rp. 60.205; and for Standar Twin rooms, Rp. 5.565.